PERAN TEKNOLOGI TEPAT GUNA UNTUK MASYARAKAT DAERAH PERBATASAN Kasus Propinsi Kepulauan Riau - Dicky Rezady Munaf; Thomas Suseno; Rizaldi Indra Janu; Aulia M. Badar (Jurnal Sosioteknologi, 2008)
The development in Indonesia's borderlands which relies on the capability of their local community in constructing appropriate technologies is one of the key factors in promoting their living standard and in boosting their self confidence. This capability, as one of the forms of the the local community empowerment, is composed of such factors as the attitude, capability and capacity level, ability to allocate their available resources, and level of understanding on technology of the local community as well as the availability of the institutional infrastructures in their local government. The borderlands may integrate the concept of appropriate technological development into their community empowerment program whose aim is to improve their local people's living standard.